Transport Costing Based on the Modelling of Technology Processes - Bokor, Z. (Acta Technica Jaurinensis, 2011)
Transport costing is a relatively seldom addressed topic of the researches and the literature. At the same time, its traditional methods are not always sufficient to determine the real costs of services and to support the evaluation of cost effectiveness. Thus the methodology needs to be developed significantly. This paper aims at working out a costing model which is able to enhance the reliability of transport cost calculations. The elaboration of the model makes advantages of the related research results published in the literature. On the other hand, it uses a new approach: connects cost allocations to the logic of technology processes. The model is verified through an illustration of a simple example.